Characterization of PM10 surrounding a cement plant with integrated facilities for co-processing of hazardous wastes. (10th June 2018) - Yang, Zhenzhou; Tang, Siqi; Zhang, Zuotai; Liu, Chongxuan; Ge, Xinlei
Abstract: The co-processing of wastes in cement production has become an irreversible trend worldwide. However, secondary pollution particularly the air pollution has rarely been investigated despite it may compromise the environmental benefits of waste utilization. In this study, we collected the atmospheric particulate matter (PM10 ) around a cement plant in Changping district in Beijing, China, which co-processes hazardous wastes and municipal sewage sludge, and investigated the characteristics of trace elements, inorganic and organic species in the samples. The results show that volatile elements (Zn, As, Se, Sc, Cd, Sb and Pb) that are abundant in the wastes can be highly enriched in PM10 compared with local soil, reflecting the influences from cement production. The water-soluble species were generally dominated by organics, which were moderately oxidized with an average oxygen-to-carbon atomic ratio (O/C) of 0.25 and an organic mass-to-organic carbon (OM/OC) ratio of 1.49. In addition, single particle imaging analyses revealed eight types of aerosol particles: S-rich, K-rich, Na-rich, fly ash, mineral, organic, metal and soot. Furthermore, the single particle analysis suggests that the metals released from the cement production may act as catalysts to promote the heterogeneous formations of sulfate and other secondary organic species. Overall, as a preliminary yet pioneering study, our findings highlight the possibly important but understudied influences of solid waste treatment processes on local air quality and haze formation. Graphical abstract: Image 1 Highlights: The chemical characteristics of PM10 collected from a cement plant co-processing hazardous wastes were investigated. Eight types of aerosol particles: S-rich, K-rich, Na-rich, fly ash, mineral, organic, metal and soot were observed. The results implied severe role of cement industry emission to the PM pollution and haze formation.